Evolution, Causes and Influence Factors of Taal Volcanic Activities. Issue 1 (1st April 2022) - Bai, Xinyuan; Xie, Shaojing; Zhu, Yanjun
Abstract: Volcanoes are a kind of geological feature which can bring both destruction and wealth to human beings. This study takes the eruption of Taal Volcano on January 12, 2020 as an example to analyze its eruption evolution, causes and influence factors via QGIS software. Taal Volcano lies at the southwestern end of a convergent boundary between the Eurasian and Philippine Sea tectonic plates where volcanic activities are frequent. Results show that the evolution of the eruption consists of increased CO2 flux, seismic swarms, phreatic explosion chronically. The origin of the volcano is the subduction of the oceanic plate and terrestrial plate. Volcanic eruptions are mostly due to pressurization by active convergent plates activities. The eruption emitted tephra and gas, which exerted impacts on the atmosphere, the nearby vegetation and the water body, and was predicted to result in an El Nino. High concentration of particles, dispersed tephra output, a sharp increase in SO2 and CO content, variation in atmospheric ozone, and rise in humidity were observed in the atmosphere following the eruption. The volcanic output wiped out the plant cover on the volcano island, and covered the vegetation outside of the volcano island, as shown in the RGB band composite and land cover change monitoring images generated using QGIS from Sentinel-2 data. The volcanic output's influences on nearby water bodies were shown through drops in ocean salinity and Taal lake's PH, variation in ocean temperature, and increased ocean's surface latent heat flux.